The association between health and prison overcrowding, a scoping review - Maha Aon; Simon Oberconz; Marie Brasholt (BMC Public Health)
Abstract It is estimated that the majority of prisons globally are overcrowded. There is consensus that overcrowding leads to negative health outcomes, however quantitative research of this association appears limited. This scoping review aimed to identify literature examining the association between prison overcrowding and health outcomes, and to summarize these associations. Two databases and a grey literature site were searched for quantitative studies where overcrowding was an independent variable, and the outcome was any physical or mental health issue. This yielded 34 records from 16 mostly high-income countries in addition to three multi-country studies. Studies applied a range of definitions of overcrowding with the most common being occupancy rates. Studies mostly concluded that overcrowding had a positive association on the outcome under study, i.e., as overcrowding increased so did the prevalence of the disease under study. When methodological limitations were taken into consideration, we found that in eighteen articles prison overcrowding was independently and positively associated with tuberculosis, COVID-19, self-harm, depression, overall prison mortality, and injuries due to violence respectively. Prison overcrowding was not found to be independently associated with suicide in four of the five studies where it featured.